Quantifying the influence of geography and environment on the northeast Atlantic mackerel spawning distribution. (10th November 2017) - Brunel, Thomas; van Damme, Cindy J. G.; Samson, Melvin; Dickey‐Collas, Mark
Abstract: Mackerel ( Scomber scombrus ) in the northeast Atlantic have shown changes in distribution at certain times of the year, which have impacted their exploitation and management. In this study, mackerel spawning habitat over 21 recent years was characterised using generalised additive modelling, based on spatial egg density data collected every third year during targeted ichthyoplankton surveys. Mackerel spawning distribution was found to depend primarily on geographical variables (coordinates and bottom depth), with preferred spawning locations on the shelf‐edge from the north of the Iberian peninsula to the west of Scotland, with a maximum west of Ireland. Environmental drivers had a lesser influence on egg distribution. Dome shaped relationships were found with temperature and mixed layer depth, with respective optimum at 13°C and around –300 m. The model was used to reconstruct maps of the potential habitat (areas where conditions were suitable, but not necessarily used, for spawning). Little changes were observed over the years in the potential habitat, suggesting that the expansion of the egg distribution (realised habitat) was not triggered by changes in the environmental variables investigated. Little evidence was found for density‐dependent habitat selection. There was a tendency for mackerel to make more use of areas of lesser suitability in years with large stock size (1992 and 2010). This pattern, however, broke down in 2013, when stock size was the highest, as spawning occurred very south and concentrated in the most suitable habitat.